Halfway Around the World: Learn the language, meet the people, eat the food. - Neville-Neil, George V. (Communications of the ACM, 2023)
The article discusses advice for an employee who is asked to relocate to another country for six months to help launch a software development group, and it mentions tips about learning the language of the country that you are going to be working in, as well as comments about meeting people and eating the local foods. According to the article, language learning increases human brain function. Cultural differences and collaboration are assessed.